2006
DOI: 10.1002/mar.20125
|View full text |Cite
|
Sign up to set email alerts
|

Marketplace and personal space: Investigating the differential effects of attachment style across relationship contexts

Abstract: An individual's tendencies in purely personal relationships seem to lead to related tendencies in consumer relationships. The following article presents a study that illustrates how individual differences in personal relationship attachment style can be used to predict the likely success of consumer relationships. In addition, it illustrates how the success of consumption versus nonconsumption relationships can be explained by the effect of attachment style on the individual's perception of qualities of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 38 publications
1
81
0
Order By: Relevance
“…The importance of identifying customers with high levels of intrinsic retainability on whom companies can focus their relationship-building efforts has been repeatedly stressed in the relationship marketing literature (Reichheld, 1996;Reinartz & Kumar, 2000). Thus, from a relationship marketing perspective, a focus on secure attachment makes sense, since customers scoring high on secure attachment should, according to the theory, be characterized by higher relationship quality and, as a consequence, also higher relationship stability, than their less securely attached counterparts (Thomson & Johnson, 2006).…”
Section: Theoretical Background On Attachment Theorymentioning
confidence: 88%
See 2 more Smart Citations
“…The importance of identifying customers with high levels of intrinsic retainability on whom companies can focus their relationship-building efforts has been repeatedly stressed in the relationship marketing literature (Reichheld, 1996;Reinartz & Kumar, 2000). Thus, from a relationship marketing perspective, a focus on secure attachment makes sense, since customers scoring high on secure attachment should, according to the theory, be characterized by higher relationship quality and, as a consequence, also higher relationship stability, than their less securely attached counterparts (Thomson & Johnson, 2006).…”
Section: Theoretical Background On Attachment Theorymentioning
confidence: 88%
“…As stated before, this study followed Shaver and Mikulincer's (2002b) suggestion to develop different measures for different purposes. Based on Thomson and Johnson's (2006) recommendation to focus on secure attachment in future research, a specific measure of secure business attachment for this specific relationship type was developed. As explained above, their recommendation is based on the fact that secure attachment is most relevant from a relationship marketing perspective.…”
Section: Business Attachmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the psychology literature, emotional attachment was used to explain close relationships between two people; the term originally referred to an individual's psychological instinct to maintain relationships with comfortable, supportive, and reliable people (Hyun and Kim, 2014). However, marketing research indicated that attachment can extend beyond personal relationships to relationships with companies, brands, and places (Park et al, 2007;Thomson and Johnson, 2006;Vaske and Kobrin, 2001;Vlachos et al, 2010;Williams and Vaske, 2003). Previous studies on attachment also indicated that consumers tend to experience strong emotional attachment when they can fulfill their needs with certain branded products that represent their self-concepts and feelings of self-connection (Fournier, 1998;Hwang and Kandampully, 2012).…”
Section: Consumers' Responses To Stores' Green Practicesmentioning
confidence: 96%
“…Attachment anxiety, specifically, relates to the degree to which individuals worry about whether they will be accepted in relationships and fear abandonment (Mikulincer & Florian, 1998;Morey et al 2013;Thomson & Johnson, 2006). Individuals with differing levels of attachment anxiety have different expectations regarding interpersonal encounters and social situations (Bartholomew & Horowitz, 1991).…”
Section: The Moderating Role Of Attachment Anxietymentioning
confidence: 98%